Assessment of mental and physical health outcomes over time in an integrated care setting - Dependra Bhatta; Monteic A. Sizer; Binod Acharya; Dipendra Banjara (BMC Primary Care)
Abstract Background Integrated care addresses the fragmentation of patient health services and potentially improves the experience of care, reduces healthcare costs, and improves health outcomes. This study assessed the improvements in mental health and physical health outcomes among patients living with mental health challenges and treated in an integrated care setting. Methods The longitudinal retrospective cohort study evaluated anxiety (GAD-7), depression (PHQ-9), systolic blood pressure, and glycated hemoglobin levels from baseline to the next three assessments recorded from October 1, 2018, to December 31, 2023. Results At baseline, 239 participants responded to mental health outcome measures, 344 to systolic blood pressure, and 164 to glycated hemoglobin level. The Generalized Estimating Equations analysis showed an improvement in GAD-7 (-1.28 [95% CI, -1.71 to -0.85]) and PHQ-9 (-1.37 [95% CI, -1.73 to -0.92]) scores in successive assessments. The physical health outcomes (Systolic blood pressure (-0.004 [95% CI, -1.34 to 1.35]) and glycated hemoglobin (0.04 [95% CI, -0.07 to 0.15])) remained stable. Conclusion This study demonstrates that patients with mental health challenges treated in integrated care experience improvements in depression and anxiety symptoms, with stable physical health outcomes.